The development and validation of Coffee Use Disorder and Coffee Addiction Scale (CUDCAS) and its correlation with insomnia and anxiety symptoms - AlSaleh, Aseel; Husain, Waqar; Ghazzawi, Hadeel; Alhaj, Omar A.; Ammar, Achraf; Trabelsi, Khaled; Jahrami, Haitham (Frontiers in Nutrition, 2025)
BackgroundCoffee is a globally consumed beverage. However, the impairments associated with its excessive use remain under-recognized. There is currently no standardized measurement for coffee use disorder based on DSM-5 application. This study describes the development and psychometric properties of the Coffee Use Disorder and Coffee Addiction Scale (CUDCAS)—a self-report tool developed specifically for this purpose.MethodsA cross-sectional survey was designed and delivered to 523 participants. Items from CUDCAS (11 items with reference cluster) indicate substance use disorder criteria taken from the DSM-5 and were rated on a three point Likert scale and used descriptive statistics; internal consistency (Cronbach's α and McDonald's ω); exploratory/confirmatory factor analysis (EFA, CFA); item response theory (IRT), and correlations with caffeine consumption, insomnia (AIS) and anxiety symptoms (GAD-7) were also examined.ResultsCUDCAS was found to be a very reliable (α and ω = 0.86) measure of coffee use disorder symptoms. CFA results supported the unidimensional factor structure of the CUDCAS and the overall model fit was good (CFI = 0.92, TLI = 0.90, RMSEA = 0.07, SRMR = 0.04). The IRT analyses further demonstrated an appropriate distribution of item difficulties, measurement of item precision and subsequently, CUDCAS as an overall measurement of coffee use disorder that is responsive to coffee consumption. CUDCAS also demonstrated significant correlations with caffeine consumption (r = 0.54), insomnia (r = 0.37), and anxiety (r = 0.32), respectively, for construct validity.ConclusionsThe findings suggest that the CUDCAS is a reliable and valid tool to assess the symptoms of coffee use disorder, and the current results provide support for its use in research and clinical settings.